Experimental study on smoke temperature distribution and thermal-driven propagation in groove-like spaces under different fan arrangements - Sinian Gu; Houyang Liu; Yang Wang; Zhichao Yu; Yunji Gao (Case Studies in Thermal Engineering)
In order to explore the fire smoke temperature and propagation characteristics of the groove space under the overpass considering different fan spacing arrangements, a series of gas fire experiments were carried out in the reduced fire experiment platform of groove-like space. Three fire source powers and four fan arrangement conditions are selected. The essential parameters in the groove space under different fire powers and fan layout spacing are obtained and analyzed, including flame shape, flame height, longitudinal temperature distribution, smoke expansion length and smoke propagation speed. The main findings are as follows: The flame height decreases with the decrease of fan spacing and heat release rate. The flame height is proportional to the 2/5 power of the heat release rate, and the proportional coefficient decreases from 10.99 to 7.80 as fan spacing decreases. The maximum smoke temperature is determined by the 2/3 power of the heat release rate and the minus 5/3 power of the ceiling height, and the fitted coefficient β changes from 18.29 to 11.02 as the fan spacing decreases. The longitudinal temperature distributions in the upstream and downstream of the fire source in the groove space are similar, and the dimensionless longitudinal smoke temperature distribution decreases exponentially with longitudinal distance, and the fitting coefficients k′ and y0 decrease as the fan spacing decreases. Under no fan and 9.0 m fan spacing conditions, the smoke expansion length is greater than 5.0 m, while when the fan spacing is 6.0 m or 3.0 m, the smoke expansion length decreases significantly. Moreover, the average smoke propagation speed increases from 0.45 m/s to 1.0–1.3 m/s as fan spacing decreases.